Factors Compel Young Generation to Indulge in Cell Phone Use - Ahmed, Mahmuda; Rahat Chowdhury, Zobaid Mohammad; Begum, Rahana; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2025)
Background: Cell phone is very important and wonderful communicative tools used by all age group people especially young generation. Extra sense of security and safety is probably one of the main reasons parents even consider getting a younger child a cell phone. This study was designed to assess perception of the people about young generations indulge in cell phone use. Methods: This descriptive cross-sectional study was conducted among 725 respondents selected purposively from areas of Dhaka North City and Dhaka South City Corporation. Relevant data were collected through face-to-face interview with the help of semi-structured questionnaire. Results: Among the total 725 respondents 63.0% were male and the rest 37.0% were female. In Bangladesh the sex ratio is 0.98 (980 males per 1,000 females). Regarding education, it was seen that most were literate (97.2%) having education from non-formal to graduation and above. Majority of the respondents (60.6%) were graduates and above and 20.8% passed higher secondary education. The literacy rate of Bangladesh in the urban area is 81.28 % while in rural area it is 71.56. The rate is higher among the male population which is 76.56%, while among female population it is 72.82%. Adult literacy rate is the percentage of people ages 15 and above whom can both read and write with understanding a short simple statement about their everyday life. One fifth (20.6%) of the respondents were service holders, 17.1% were students, 15.7% were doctors, and 14.1% were businessmen. Conclusion: Cell phone becomes most popular in adolescence students for special feature like social networking and gaming service. Although cell phone is useful and convenient, adolescences are dependent on cell phone more and more for unnecessary communication. Considering its negative impact of cell phone over use on physical and psychosocial health, public health programs should develop preventive strategies. JOPSOM 2023; 42(2): 1-6